2019
DOI: 10.1039/c9ra07258f
|View full text |Cite
|
Sign up to set email alerts
|

Nickel foam and stainless steel mesh as electrocatalysts for hydrogen evolution reaction, oxygen evolution reaction and overall water splitting in alkaline media

Abstract: Efficient electrocatalytic overall water splitting is achieved with commercially-available and low-cost nickel foam and stainless steel mesh as cathode and anode electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(108 citation statements)
references
References 55 publications
8
100
0
Order By: Relevance
“…1b) confirmed that the nickel foam has three dimensions structure with many pores and a rough surface. The physical properties produced in this study were very similar to those reported by [9]. Further characterization with XRD (Fig.…”
Section: Pretreatment Of Nickel Foamsupporting
confidence: 86%
See 1 more Smart Citation
“…1b) confirmed that the nickel foam has three dimensions structure with many pores and a rough surface. The physical properties produced in this study were very similar to those reported by [9]. Further characterization with XRD (Fig.…”
Section: Pretreatment Of Nickel Foamsupporting
confidence: 86%
“…Further characterization with XRD (Fig. 1c) shows that nickel foam observed three diffraction peaks of 2θ, namely 44.5°, 51.9°, and 76.4° on the index (111), (200), and (220), which corresponded to the reference diffraction values of PDF # 04-0850 [9].…”
Section: Pretreatment Of Nickel Foammentioning
confidence: 75%
“…Later it has, however, been shown that the Ni-foam itself contributes to the electrocatalytic activity. [21] The focus of this study is not reducing the overpotential to the minimum value. Instead, we want to gain insights into the effect of grafting on the overpotential by comparing the performance of three distinct Ni and Co brucite-derived layered structures, namely, (i) brucite M(OH) 2 without any interlayer anions, (ii) LDHs with free interlayer anions and (iii) hydroxynitrates with grafted interlayer anions.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of anode catalyst price suggests that it would be beneficial for a commercial electrolyser to have an anode catalyst based on abundant metals which could show similar catalytic performance to that of a precious anode catalyst (IrO2-based). Potential alternatives to IrO2-based anode catalyst could nickel-based 82,83 anodes.…”
Section: Developing Lower Cost Anode Catalysts and Anion Exchange Membranesmentioning
confidence: 99%